Peran Mahasiswa Kampus Mengajar dalam Meningkatkan Kualitas Penyelenggaraan Pendidikan Berbasis Teknologi di Sekolah Dasar - Khairul Amri; Udik Budi Wibowo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The objective of this study is to describe the role of university students in improving the quality of technology-based education in elementary schools through the kampus mengajar program. This qualitative research employed a phenomenological approach and was conducted in three partner schools located in Ngaglik, Sleman, Yogyakarta: SDN Ngebelgede II, SDN Brengosan II, and SDN Clumprit. Research subjects included Kampus Mengajar students, principals, mentor teachers, and field supervisors (DPL). Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles & Huberman interactive model. Data validity was ensured through source and technique triangulation. Findings show that the roles of kampus mengajar students fall into three key aspects: as educators and facilitators of technology-based learning, administrative assistants, and technology literacy instructors for teachers. Students contributed to improving students’ literacy and numeracy using tools such as animated videos, canva, and the AKM assessment. They also supported administrative tasks, including grade processing, formatting documents, and developing school media. Teacher technology literacy training was implemented at SDN Clumprit through the use of moodle, as part of the broader effort to support digital transformation in elementary education.